Using Social Media Applications in Active Collaborative Learning to Engage Learners’ Performance in Learning - Puttipong Anantasopon; Singha Chaveesuk (My University, 2022)
Social Media Application has become popular to adopt during the COVID-19 pandemic. The social media is ultimate devices to encourage students’ engagement and active collaboration learning. This study tested the proposed framework. 140 learners in higher education in Thailand have been examined in this study. The PLS-SEM was used to analyze the data obtained. Convergent and discriminant analysis were used to measure the different variables. This study proved that all variables are supported to use social media application, which lead the learners have better performance in learning.
Keywords: Innovative Teaching and Learning Methods; Impact of Technology on Adolescents; Knowledge Management and Sharing